Forensic view on two Raspberry Shake burglargrams - Klaus-G. Hinzen; Heinrich Krummel; Bernd Weber; Claus Fleischer (Journal of Seismology, 2022)
A steadily increasing number of citizen seismological stations, often located in populated areas, record a plethora of man-made events. These events are especially of interest, when they are caused by criminal activity or man-made explosions. On 4 December 2021, during an attempted robbery of an automated teller machine (ATM) in Bonn-Röttgen, Germany, the burglars used explosions. The seismic effects of the explosions were recorded with a Raspberry Shake (RS) station at a distance of 580 m from the site. While working on the analysis of this signal, another attack on an ATM on 23 February 2022 in Kürten-Dürscheid was recorded by another RS station, this time at 830-m distance with an instrument that also included an air pressure channel. The seismic signatures of both events indicate similar procedures in both cases whereby a larger explosion was quickly followed a smaller explosion after 21 s and 49 s, respectively. An estimate of the charge weight of the explosions shows that ratios of the strength of the first to second explosion were 21:1 and 9.4:1 in the Röttgen and Dürscheid attacks, respectively.